Emotion Recognition in Human-Computer Interaction - Cowie, Roddy I D; Douglas-Cowie, Ellen; Tsapatsoulis, Nicolas; Votsis, George; Taylor, John G.; Kollias, Stefanos D.; Fellenz, Winfried A. (My University, 2001)
Two channels have been distinguished in human interaction: one transmits explicit messages, which may be about anything or nothing; the other transmits implicit messages about the speakers themselves. Both linguistics and technology have invested enormous efforts in understanding the first, explicit channel, but the second is not as well understood. Understanding the other party's emotions is one of the key tasks associated with the second, implicit channel. To tackle that task, signal processing and analysis techniques have to be developed, while, at the same time, consolidating psychological and linguistic analyses of emotion. This article examines basic issues in those areas. It is motivated by the PKYSTA project, in which we aim to develop a hybrid system capable of using information from faces and voices to recognize people's emotions.
Keywords: Human-Computer interaction